Peer-to-peer Lecture Films – A Successful Study Concept for a First Year Laboratory Material Science Course. (20th July 2016) - Pfennig, Anja; Hadwiger, Paul
Abstract: Material science is believed to be one of the more complicated subjects in mechanical engineering because the scientific background is generally not taught at school during job training. First year students of mechanical and automotive engineering at HTW Berlin are required to take 2 classes in material science. Laboratory exercises accompany the education, but basic knowledge upon theory is necessary to work practically. Lecture films show the laboratory routine prior to lab hours and show students what they are going to experience and learn. These films were initially inspired by students and conducted during a one term semester project supervised by lecturers and film experts (peer-to-peer approach). It was found that students watching the films were prepared better and gained more knowledge during practical work than those who did not have access to the films. Watching the introductory films lead to more download activity and actual studying of the lectures provided to prepare the experiments and furthermore lead to slightly better testing results. Peer-to-peer lecture films were also successfully implemented teaching general phase diagrams and the iron-carbon-phase diagram.